A novel force sensing system for research on shot-put techniques - Song, G.; Song, A.; Ge, Y. (IEEE International Conference on Information Acquisition, 2005)
Paper presents a novel force sensing system for measuring the forces applied on a shot by shot-put athletes. A shot-put sensor with almost the same size and weight as the standard shot for open males has been designed and fabricated. The sensor can simultaneously detect applied forces along three orthogonal directions. Instead of using a common shot, the shot-putters can use this shot-put sensor to make their throws. With the help of a commercially available high-speed photography system, field tests have been performed. The experimental results show that the force sensing system is effective in getting the force information of the shot-put athletes. In this manner, the force sensing system serves as a powerful tool for coaches and sports scientists to make scientific researches on shot-put techniques. It also provides an intuitive and reliable guidance for the shot-put athletes to improve their skills.